Dynamic resources management of virtual appliances on a computational cluster - Moskovsky, A.A.; Pervin, A.Yu.; Walker, B.J. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2008)
The virtual machine (VM) technology offers an increased flexibility in resource provisioning. The load for applications typically varies over time, justifying a need for the dynamic resource allocation/relinquish mdash; exactly what the VM technology allows. We have devised an approach for the automated dynamic resource management of applications running on a computational cluster. A job of the framework is to maintain a certain service level of an application within tolerable limits. To accomplish this, the framework is able to dynamically vary resources available to the application. To facilitate the performance optimization, an application performance profile can be created using stress-testing tools. We have created a software toolkit that allows running single and multiple VM applications. Sample services (including both computing oriented and web oriented) have been tested and performance-resource dependences studied. We present an ongoing work on dynamic resource allocation, involving optimal control and optimization methods. The paper was prepared on the basis of the authors’ report at the International Conference on Parallel Computing Technologies (PaVT-2008; http://agora.guru.ru/pavt2008).